Achieving a good impression: Reputation management and performance goals. Issue 4 (10th January 2021) - Good, Kayla; Shaw, Alex
Abstract: Whether a student wants to improve their ability (i.e., has learning goals) or demonstrate it (i.e., has performance goals) plays an important role in their learning and motivation; students focused on the latter tend to avoid taking on challenges and seeking help when they need it. In the achievement literature, these different goals are thought to result primarily from holding different mindsets about whether one's ability is malleable or fixed. We argue, however, that this traditional framework has largely overlooked the powerful role that reputational concerns play in influencing which achievement goals students pursue. Specifically, reputational concerns may drive students to pursue performance goals and "prove" their ability to others, irrespective of their mindsets. We argue that closely investigating these concerns may help uncover new mechanisms by which performance goals are fostered and maintained as well as new strategies for developing interventions aimed at encouraging learning goals. Finally, we offer suggestions for how the achievement and reputation management literatures can be productively brought to bear on one another in future research. This article is categorized under: Psychology > Reasoning and Decision Making Psychology > Emotion and Motivation Psychology > Development and Aging Abstract : Reputational concerns for appearing "smart" to others can drive students to focus on performance goals rather than learning goals, irrespective of their mindset.